How does emotion regulation affect adolescents' social adaptability? Building bridges for parent-child communication, empowered by AI education - Entao Ma; Tinghong Lai; Yuri Lee; Yixuan Zhang; Shimin Fu (Acta Psychologica)
Although emotion regulation (ER) is known to enhance social adaptability (SA) in adolescents, the underlying family mechanisms and impact of educational technologies remain unclear. This study investigated the mediating roles of parent-child communication (PCC) and parent-child relationship (PCR), along with the moderating effect of AI education (AIEd) experience. Data from 1318 Chinese adolescents were analyzed using structural equation modeling with bootstrapping and multi-group comparison. Key findings show that: (1) ER significantly and positively predicted SA; (2) PCC mediated the relationship between ER and SA, whereas PCR showed no significant mediation; (3) The PCC to PCR chain mediation in the effect of ER on SA was non-significant; (4) Crucially, AIEd experience amplified two pathways: ER to PCC and PCC to SA, indicating dual-path enhancement. These findings reveal that PCC—but not PCR—serves as the core family mechanism translating ER into SA in Chinese adolescents. Notably, AIEd experience strengthens both the transformation of emotion regulation into family communication and the application of communication skills to social adaptation. This suggests that people should make family communication concretely rather than generalize family relationships, and pay attention to the functional design of AIEd tools to make up for the digital gap. This study provides empirical support for the application of AI technology in education, helping educators and policymakers to better understand the impact of the application of AI technology in education and develop evidence-based strategies to improve Chinese adolescents' social adaptability.